Provável sarcopenia de acordo com o consenso EWGSOP2 em idosos atendidos pela Estratégia Saúde da Família (ESF) da região de Campinas-SP : Probable sarcopenia according to the consensus EWGSOP2 in older adults attended by the Family Health Strategy (FHS) of the region of Campinas-SP - Silva, Graziele Maria da, 1993- (2020)
Orientador: Ligiana Pires Corona